Metasomatic alteration of type 3 ordinary and carbonaceous chondrites - Krot, Alexander N.; Petaev, M. I.; Piani, L.; Marrocchi, Y.; Fujiya, W.; Pravdivtseva, O. V.; Dobrică, E.; Vacher, L. G.; King, A. J.; Lee, M.; Van Kooten, E.; Jacobsen, B.; et al. (Space science reviews, 2025)
Metasomatism refers to the process during which a pre-existing rock undergoes compositional and mineralogical transformations associated with chemical reactions triggered by the reaction of fluids which invade the protolith. It changes chemical compositions of minerals, promotes their dissolution and precipitation of new minerals. In this paper, we review metasomatic alteration of type 3 ordinary (H, L, LL) and carbonaceous (CV, CO, CK) chondrites, including (i) secondary mineralization, (ii) physicochemical conditions, (iii) chronology (53Mn-53Cr, 26Al-26Mg, 129I-129Xe) of metasomatic alteration, (iv) records of metasomatic alteration in H, O, N, C, S, and Cl isotopic systematics, (v) effects of metasomatic alteration on O- and Al-Mg-isotope systematics of primary minerals in chondrules and refractory inclusions, and (vi) sources of water ices in metasomatically altered CV, CO, and ordinary chondrites, and outline future studies.
Gesehen am 21.07.2025